The role for surgery in IDH-mutant grade 4 Astrocytomas: interactive effects of resection, patient characteristics, and outcome - report of the RANO resect group - Philipp Karschnia; Gilbert Youssef; Jacob S Young; Nico Teske; Maarten M J Wijnenga; Antonio Dono; Okizeva Rapi; Yae Won Park; Arthur Wagner; Tommaso Sciortino; Francesco Bruno; Levin Häni; et al. (Neuro-Oncology, 2026)
Lay Summary Surgery is the first step in treating patients with the rare brain tumor IDH-mutant grade 4 astrocytoma. In an international study of 266 patients, we examined how the amount of tumor remaining after surgery affects survival. Patients with less remaining contrast-enhancing tumor lived longer. Those who underwent ‘supramaximal’ surgery (tumor removal beyond the visible enhancing portion) had the most favorable outcomes. Loss of the CDKN2A/B gene was linked to worse survival regardless of the extent of surgery. These findings suggest that removing as much enhancing tumor as safely possible may improve outcomes and guide risk stratification in future clinical trials.